REFORMULASI PELAYANAN PEMBUATAN AKTE KELAHIRAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SERANG - Amilia, Rizki; Alwajir, Dede Qodrat; Prahima, Parko; Fajarwati, Noerma Kurnia; Arasid, Mohamad Ikrom (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Delays in the production of birth certificates can have a negative impact on children's civil rights. This research aims to improve the quality of birth certificate processing services at the Disdukcapil of Serang Regency to make it faster, easier and more affordable for the community. Through a series of analyses and evaluations, several innovative solutions were found that can be implemented. With this reformulation, it is expected that the community can obtain their children's birth certificates more quickly, so that children can access various public services such as education and health without obstacles. The type of research used in this study is descriptive research with a qualitative approach. The location of this research is Serang District. Through in-depth analysis of existing processes, identification of barriers, and comparative studies with other regions, several improvement recommendations were made. These recommendations include simplification of procedures, utilisation of information technology, increased officer capacity, and more effective socialisation to the community